Emotion displays in media: a comparison between American, Romanian, and Turkish children's storybooks - Wege, Briana Vander; Sánchez González, Mayra L.; Friedlmeier, Wolfgang; Mihalca, Linda M.; Goodrich, Erica; Corapci, Feyza (Frontiers in Psychology, 2014)
Children's books may provide an important resource of culturally appropriate emotions. This study investigates emotion displays in children's storybooks for preschoolers from Romania, Turkey, and the US in order to analyze cultural norms of emotions. We derived some hypotheses by referring to cross-cultural studies about emotion and emotion socialization. For such media analyses, the frequency rate of certain emotion displays can be seen as an indicator for the salience of the specific emotion. We expected that all children's storybooks would highlight dominantly positive emotions and that US children's storybooks would display negative powerful emotions (e.g., anger) more often and negative powerless emotions (e.g., sadness) less often than Turkish and Romanian storybooks. We also predicted that the positive and negative powerful emotion expressions would be more intense in the US storybooks compared to the other storybooks. Finally, we expected that social context (ingroup/outgroup) may affect the intensity emotion displays more in Turkish and Romanian storybooks compared to US storybooks. Illustrations in 30 popular children's storybooks (10 for each cultural group) were coded. Results mostly confirmed the hypotheses but also pointed to differences between Romanian and Turkish storybooks. Overall, the study supports the conclusion that culture-specific emotion norms are reflected in media to which young children are exposed.